Assessing usability and satisfaction of telephone-based psychiatry consultations in Oman: a cross-sectional study - Tamadhir Al-Mahrouqi; Fatema Al-Sabahi; Mohammed Al-Alawi; Munira Al Rubkhi; Marwa Al Abdali; Muna Al Salmi; Tharaya Al-Hashemi; Rahma Al Nuumani; Fatma Al Balushi; Rashid Al Zaidi; Samir Al-Adawi; Sachin Jose; et al. (Frontiers in Digital Health, 2025)
BackgroundTelehealth has become a valuable tool for providing health services remotely through digital communication technologies. Therefore, assessing patients' satisfaction and the utility of this tool is crucial for future implementation and development.MethodsA cross-sectional survey study was conducted at Al Masarra Hospital between January 1st, 2023, and June 30th, 2023, with adults recruited from the general adult psychiatry clinic and received at least 3 previous telephone-based psychiatry consultations. Data were then analyzed using the Chi-square test and a multivariate binary logistic regression.ResultsAmong 222 patients (a mean age = 37.72 years), the majority (77.5%) were found to have an overall satisfaction with the service. Most participants agreed that telehealth improves access to healthcare services (65.2%), saves time traveling (78.4%), and meets their healthcare needs (75.7%). A total of 22.5% of participants reported dissatisfaction with the service. Significant predictors of satisfaction included sex, employment status, and monthly income. Females were more likely to be satisfied with telephone-based psychiatric consultations (Adjusted OR = 2.525, p = 0.030). Homemakers or unemployed participants were more likely to report satisfaction (Adjusted OR = 7.838, p = 0.009), as were those earning between 150 and 499 OMR (Adjusted OR = 10.967, p = 0.001) and ≥500 OMR (Adjusted OR = 46.312, p < 0.001).ConclusionTelephone-based psychiatry consultations demonstrated high usability, satisfaction, and accessibility among study participants. Sex, employment status, and monthly income significantly influenced satisfaction levels. These findings highlight the potential of telehealth to bridge gaps in mental healthcare delivery, particularly for underserved populations in Oman. It is important to consider, however, the issues that might arise during these consultations that lead to dissatisfaction in some patients, and find suitable solutions for both the patients and the healthcare providers.